Geography and Development. - Henderson, J; Shalizi, Z; Venables, A (2001)
Economic development and underdevelopment is one aspect of the uneven spatial distribution of economic activity. This paper reviews existing literature on geography and development, and argues that rigorous theoretical and empirical analysis is needed to increase understanding of the role of geography in development and to better design development policy. The analytical issues are: why does economic activity cluster in centers of activity? How do new centers develop? And what are the consequences of remoteness from existing centers? Empirical evidence comes both from the international context and from studies of internal economic geography and urbanization.